A profile of the urban poor in Malaysia - Yahaya, Nurizan (Taylor & Francis, 1991)
Poverty is one of the major problem faced by Malaysia and has been given a special emphasis in the New Economic Policy (NEP). The poverty rate has decreased in 1984 (18.7 %) compared to 1976 (39.6%) and 1910 (49.4%) (Third Malaysia Plan. TMP p.104). Nevertheless, the rural poverty especially in 'the agricultural sector is still high (24.7%) in 1984 as compared to urban poverty (8..2%). The urban poverty-rate bas decreased in 1984 coinpared to 1976 and 1970. Nevertheless, by looking at the number, of households involved. -it is found that thenumber of urban poor has increased from 85,000 (1970) to 94.906 (1976) and decreased to 81,300 (1984). This trend shows that the total number of urban poor does ,not expC;rience-much change. partially as a result of migration of the rural poor. The migrariorrprocess is in accordance with one of the NEP objectives to encourage more rural Bumiputras (sons of the soil) to be involved in the modem sector and to restructure the urban ethnic distribution. This phenomena also shows that rural poverty is a serious problem, thus forcing a majority of the youths to migrate in search of a better life in the cities,